Prenatal diagnosis in severe cases: a new gain in Portuguese neonatal - Sousa, Carmen (2011)
Introduction The expansion of the Portuguese neonatal screening since 2004, based on MS/MS technology, allows the tracing of 25 diseases in all Portuguese newborns in one single laboratory. Following this expansion, the molecular study was also implemented for most diseases, thus allowing confirmation and prenatal diagnosis in severe cases. Methods Five prenatal diagnoses were made in pregnant women who had children affected with severe forms of CPT2 deficiency, ARG1 deficiency, MAD deficiency and LCHAD deficiency. Disease-causing mutations were previously identified in the index patients. Genomic DNA was isolated from whole blood, cultured amniotic fluid cells or chorionic villous tissue by standard methods. Mutations were detected through direct sequencing of PCR products, performed on an automatic sequencer. Results Three prenatal diagnoses were performed on mothers with affected children, found through neonatal screening: CPT2D, MADD and LCHADD. Two other prenatal diagnoses for ARG1D were requested from Italy and France Centers. Results revealed two affected fetus and two heterozygous carriers. One of the studies is still in progress. Discussion Molecular prenatal diagnosis for severe forms can establish the diagnosis in the first trimester of pregnancy. Nevertheless, this procedure is conditioned by prior knowledge of responsible mutations in the index cases.